Migrant returns : Manila, development, and transnational connectivity - Pido, Eric J. (Duke University Press, 2017)
Eric J. Pido examines the complicated relationship between the Philippine economy, Manila's urban development, and Filipino migrants visiting or returning to their homeland, showing migration to be a multidirectional, layered, and continuous process with varied and often fraught outcomes.